Semantic and pragmatic range of football vocabulary and phraseology in the metaphorical use (based on the language of the Ukrainian press) - Пустовалова, Віра Іванівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
In the article the features of linguocultural representation of the football game as a component of sport games subcode are considered. We determine the role of lexical and phraseological group that directly relates to football in the total structure of the subcode. The functions of the word football as a means to implement the relevant concept are outlined. The analysis of expressive and axiological possibilities of concrete lingoucultural units is done. The functional specificity of these units depending on the subject of publication is determined.